How cultural orientation and self-compassion shape objectified body consciousness for women from America, Belgium, Russia, and Thailand. Issue 7 (3rd October 2021) - Wollast, Robin; Riemer, Abigail R.; Gervais, Sarah J.; Grigoryan, Lusine; Bernard, Philippe; Klein, Olivier
ABSTRACT: According to objectification theory, being treated as an object leads women to engage in self-objectification, which in turn increases body surveillance and body shame, impairing women's mental health. While most studies focusing on self-objectification rely heavily on Western populations that emphasize individualism, the current work investigates the phenomenon of body surveillance and body shame in a cross-cultural framework, involving a comparison between American, Belgian, Russian, and Thai women ( N = 605). This study aims to highlight two predictors – cultural orientation and self-compassion. Results indicate that greater endorsement of vertical individualism is related to body surveillance for American, Belgian, and Russian women; however, this relation occurred in the opposite direction for Thai women. Moreover, Americans' higher levels of body surveillance and body shame coexist with less self-compassion, whereas the reverse was true for Thais. We also tested a complementary moderation model and found that the relation between body surveillance and body shame was moderated by self-compassion, further pointing to the important role of self-compassion in the model posited by objectification theory. As a result, discussion centers on a call for future research to more closely examine how self-objectification and its correlates unfold among women of various cultural backgrounds.